2013
DOI: 10.1016/j.tet.2013.04.041
|View full text |Cite
|
Sign up to set email alerts
|

Total syntheses of the squalene-derived halogenated polyethers ent -dioxepandehydrothyrsiferol and armatol A via bromonium- and Lewis acid-initiated epoxide-opening cascades

Abstract: Herein we describe in full our investigations leading to the first total syntheses of ent-dioxepandehydrothyrsiferol and armatol A. Discovery of a bromonium-initiated epoxide-opening cascade enabled novel tactics for constructing key fragments found in both natural products and have led us to revise the proposed biogeneses. Other common features found in the routes include convergent fragment coupling strategies to assemble the natural products’ backbones and the use of epoxide-opening cascades for rapid const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 71 publications
1
12
0
Order By: Relevance
“…Starting from nerol, Sharpless asymmetric epoxidation afforded the epoxide (2 S ,3 R )- 4 in a disappointing 74% ee, a result which is nevertheless in accordance with the reported values: 70–94% [ 25 30 ] ( Scheme 4 ). Applying the same ring-opening reaction to epoxide (2 S ,3 R )- 4 , triol (2 S ,3 S )- 3 was obtained in high yield but a 6% loss in enantiomeric excess was observed (see Supporting Information File 1 ).…”
Section: Resultssupporting
confidence: 89%
“…Starting from nerol, Sharpless asymmetric epoxidation afforded the epoxide (2 S ,3 R )- 4 in a disappointing 74% ee, a result which is nevertheless in accordance with the reported values: 70–94% [ 25 30 ] ( Scheme 4 ). Applying the same ring-opening reaction to epoxide (2 S ,3 R )- 4 , triol (2 S ,3 S )- 3 was obtained in high yield but a 6% loss in enantiomeric excess was observed (see Supporting Information File 1 ).…”
Section: Resultssupporting
confidence: 89%
“…Thus compound 2 was determined as a 8,13-seco product of 1 . Compound 2 has been synthesized as a side product [23]. The mostly identical 1D and 2D NMR data of 3 and 2 indicated that they both take the same planar structure.…”
Section: Resultsmentioning
confidence: 99%
“…Geometrical configurations of double bonds ∆ 8 in 2 and 3 were both deduced as E geometry, which was deduced from NOE correlations of H 3 -16/H 2 -7 and H 2 -10/H-8, and from the chemical shifts of C-16 (<20 ppm, a methyl resonance appearing at a chemical shift less than 20 ppm is indicative of an ‘ E ’ configuration, whereas a value larger than 20 ppm indicates a ‘ Z ’ configuration) [24]. Comparisons of chemical shifts of H 3 -17 in 2 ( δ H 1.02; C 6 D 6 ) and 3 ( δ H 0.74; C 6 D 6 ) with that of the synthesized erythro 8,13-secocavernosine ( δ H 1.08; C 6 D 6 ) revealed 2 possessing a erythro -type relative configuration for the C-4–C-5 fragment [23]. While chemical shifts of Me-17 in 3 ( δ H 1.14 vs. δ H 1.26 in 2 ; CDCl 3 ) was in agreement with that of the synthesized threo -type analog [( S )-5-(( S )-2-hydroxy-6-methylhept-5-en-2-yl)-dihydrofuran-2(3H)-one] ( δ H 1.16; CDCl 3 ) [25].…”
Section: Resultsmentioning
confidence: 99%
“…Forschungsartikel course of the cyclization step was studied by changing the acetate group to aB oc group.T he introduction of the Boc protecting group is known to generate at erminating nucleophile for acid-promoted cascades. [20] In this case,w hen the Nicholas reaction was performed with linear precursor 16, with the propargylic alcohol as acetate and the primary alcohol as Boc, the cyclic carbonate ent-cis-17 was obtained exclusively (Scheme 5). Gratifyingly,a fter transformation of ent-cis-17 to the dibenzoate ent-cis-13 we found that the enantiomeric purity of epoxide 10 was completely transferred.…”
Section: Angewandte Chemiementioning
confidence: 99%